2008
DOI: 10.1002/ajmg.b.30852
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and association analyses of the phosphodiesterase 4B (PDE4B) gene in major depressive disorder in the Japanese population

Abstract: The phosphodiesterase 4B (PDE4B) interacts with disrupted-in-schizophrenia 1 (DISC1), which is a known genetic risk factor for schizophrenia, bipolar disorder and major depressive disorder (MDD). PDE4B is also important in the regulation of cAMP signaling, a second messenger implicated in learning, memory, and mood. In this study, we determined mRNA expression levels of the PDE4B gene in the peripheral blood leukocytes of patients with MDD and control subjects (n = 33, each). Next we performed two-stage case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…They found four variants in the PDE4B3 isoform nominally associated with schizophrenia in females, and four additional single nucleotide polymorphisms associated with positive symptom scores according to Positive And Negative Symptoms Scale (PANSS) testing of patients. Similar results were found in the PDE4B gene in a Japanese population, lending further support to the theory that certain PDE4B variants have a positive association with schizophrenia (Numata et al, 2009). Up-regulation of PDE4A and 4B mRNA has been observed in the frontal cortex of patients with schizophrenia (Fatemi et al, 2009).…”
Section: Associated Phenotype Referencessupporting
confidence: 83%
See 2 more Smart Citations
“…They found four variants in the PDE4B3 isoform nominally associated with schizophrenia in females, and four additional single nucleotide polymorphisms associated with positive symptom scores according to Positive And Negative Symptoms Scale (PANSS) testing of patients. Similar results were found in the PDE4B gene in a Japanese population, lending further support to the theory that certain PDE4B variants have a positive association with schizophrenia (Numata et al, 2009). Up-regulation of PDE4A and 4B mRNA has been observed in the frontal cortex of patients with schizophrenia (Fatemi et al, 2009).…”
Section: Associated Phenotype Referencessupporting
confidence: 83%
“…The Hdh mouse models of HD exhibit anhedonia and decreased socializing behaviours, which are considered to be analogous to human depression (Kennedy et al, 2005). Genetic factors, or heritability, contribute 40 -50% to the probability a person will suffer major depressive disorder (Numata et al, 2009). Changes in the mRNA expression or the activity of certain PDEs can contribute to major depressive disorder etiology.…”
Section: Changes In Phosphodiesterase 4 Mrna Expression But Not Allementioning
confidence: 99%
See 1 more Smart Citation
“…However, the present study sample was reasonable stable receiving mostly outpatient treatment, which makes such type 1 errors less likely, and genetic associations to subgroups of SZ based on PANSS scores have been reported earlier [DeRosse et al, 2006]. At the time of choosing the tagSNPs in this study, the three other association studies investigating PDE4B and SZ had not been published [Pickard et al, 2007;Fatemi et al, 2008;Numata et al, 2008a]. Therefore, the overlap between SNPs investigated in the present and published PDE4B studies is limited.…”
Section: Discussioncontrasting
confidence: 47%
“…PDE4B is highly expressed in blood fractions and nervous system tissues in humans (Cheung et al, 2007). Some clinical studies have shown that PDE4B mRNA levels in patients with MDD were down-regulated after chronic treatment with a selective serotonin re-uptake inhibitor (fluoxetine) or tricyclic antidepressant (desipramine, rolipram) (Dlaboga et al, 2006;Numata et al, 2009). In addition, chronic administration of fluoxetine increased hippocampal neurogenesis and decreased the expression of PDE4B in mice and rats (Encinas et al, 2006).…”
Section: Discussionmentioning
confidence: 98%